Democratization and women’s representation in presidential cabinets: evidence from East and Southeast Asia - Lee, Don S.; Park, Soonae (Taylor & Francis, 2018)
This article examines patterns of women’s cabinet representation across all presidential democracies in East and Southeast Asia since democratization. It demonstrates how the choice of female ministers differs across career backgrounds in presidential systems and further examines why young presidential systems in Asia are conducive to women’s access to ministerial power through professional career tracks. We argue that despite women’s successful performance in national legislative elections, women have been restricted to access the power resources necessary to target other political goals, such as cabinet positions, whereas democratic transition has provided broader avenues for women to emerge as professionals outside party politics. By analyzing original data on female ministers in East and Southeast Asia, the study finds that the share of women among professional ministers has increased over time, but women’s share among political ministers has not changed significantly. Additionally, the different qualifications of female politicians and professionals also make them eligible for appointment to different types of policy areas in terms of prestige and gender. Our analysis suggests that women’s cabinet representation has improved overall since democratic transition in Asia, but this improvement disguises contrasting outcomes in women’s cabinet status according to their career backgrounds.